Pengaruh Faktor Sosial Ekonomi Terhadap Pendapatan Petani Pinang Kering (Areca catechu L.) Di Kampung Wono Sari Kecamatan Tamiang Hulu Kabupaten Aceh Tamiang - Elsa Evita; Rozalina Rozalina; Muslimah Muslimah (Jurnal Penelitian Agrisamudra, 2021)
This study aims to analyze the effect of socio-economic factors on the income of dry betel nut (Areca catechu L.) farmers in Wono Sari Village, Tamiang Hulu District, Aceh Tamiang Regency. The sampling technique used was the saturated sampling method. Saturated sampling method is a sampling technique when all members of the population are used as samples. The number of samples in this study were 30 dried betel nut farmers in Wono Sari Village, Tamiang Hulu District, Aceh Tamiang Regency. The data used in this study are primary data and secondary data. To determine the effect of socio-economic factors on the income of dry betel nut (Areca catechu L.) farmers in Wono Sari Village, Tamiang Hulu District, Aceh Tamiang Regency, statistical analysis was used with the multiple linear regression method. Data processing was carried out using SPSS version 20 computer software. The results of this study indicate that the variable level of education and other types of work have a significant effect on the income of Dry Pinang Farmers (Areca catechu L.) in Wono Sari Village, Tamiang Hulu District, Aceh Tamiang Regency. and the variables of residence and position in the community have no significant effect on the income of Dry Pinang Farmers (Areca catechu L.) in Wono Sari Village, Tamiang Hulu District, Aceh Tamiang Regency.